Grandparents Raising Grandchildren: Navigating the System Part 2 - Legal Issues - Millie Ferrer; Angela Falcone (EDIS, 2002)
This document is FCS 2189-Eng, one of a series of the Department of Family, Youth, and Community Sciences, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication date: January 2002. Its goal is to provide grandparents with information about Florida’s legal system as it relates to grandparents raising grandchildren.